Telmisartan Quality Control by Validation of UV-Spectrophotometric Method - Tsvetkova, Dobrina; Obreshkova, Danka; Ivanova, Stefka; Yankov, Vladimir; Atanasov, Peter; Hadjieva, Bozhidarka (International Journal of Innovative Research in Medical Science, 2016)
The aim of current study was to validate spectrophotometric method with UV-detection for identification and determination of Telmisartan in 99.8 % ethanol in respect of analytical parameters: selectivity, linearity, limit of detection (LOD), limit of quantification (LOQ), accuracy and precision (repeatability). For Telmisartan in 99.8 % еthanol at λ max = 298 nm for A1%1cm and ε the obtained results for А > 0.2 and А < 0.2 are: 1) А > 0.2: at 3.10–6 g/ml ÷ 1.25.10–5 g/ml; A1%1cm: 725 ÷ 823; ε: 37347 ÷ 42335 2) А < 0.2: at 2.5.10–7 g/ml ÷ 1.10–6 g/ml; A1%1cm: 1201 ÷ 1567; ε: 61816 ÷ 80651 Analytical parameter accuracy is represented by the degree of recovery, which in the corresponding confidence possibility suit the confidence interval: R СТ60: 100.31 % ÷ 102.05 %; R СТ80: 99.22 % ÷ 103.18 %; R СТ100 : 93.58 % ÷ 101.9 %. For precision is proved that all results for the quantities correspond to the relevant confidence interval: СТ60: 60.31 mg ÷ 60.77 mg; СТ80: 79.82 mg ÷ 82.18 mg; СТ100: 94.22 mg ÷ 101.58 mg.